Cardiac Magnetic Resonance Imaging in the Evaluation and Prognosis of Infiltrative Cardiomyopathies - Merna Hussien; Francisca Bermudez; Patrick T. Bering; Gaby Weissman; Allison G. Hays; Farooq H. Sheikh (Journal of Cardiovascular Development and Disease)
Advancements in cardiac magnetic resonance (CMR) imaging quality and availability have made it an essential tool in the care of individuals living with cardiomyopathies. CMR complements clinical suspicion, electrocardiogram patterns, and echocardiographic findings to help elucidate the etiology of cardiomyopathies and can also be used to prognosticate and follow treatment responses. In this review, we highlight the common CMR findings in cardiac amyloidosis, cardiac sarcoidosis, iron overload cardiomyopathy, and Fabry disease. We also summarize prognostic findings and additional potential roles for CMR in the management of infiltrative cardiomyopathies.